Video delivery networks: Challenges, solutions and future directions. (February 2018) - Fan, Qilin; Yin, Hao; Min, Geyong; Yang, Po; Luo, Yan; Lyu, Yongqiang; Huang, Haojun; Jiao, Libo
Abstract: Internet video ecosystems are faced with the increasing requirements in versatile applications, ubiquitous consumption and freedom of creation and sharing, in which the user experience for high-quality services has become more and more important. Internet is also under tremendous pressure due to the exponential growth in video consumption. Video providers have been using content delivery networks (CDNs) to deliver high-quality video services. However, the new features in video generation and consumption require CDN to address the scalability, quality of service and flexibility challenges. As a result, we need to rethink future CDN for sustainable video delivery. To this end, we give an overview for the Internet video ecosystem evolution. We survey the existing video delivery solutions from the perspective of economic relationships, algorithms, mechanisms and architectures. At the end of the article, we propose a data-driven information plane for video delivery network as the future direction and discuss two case studies to demonstrate its necessity.